1969
DOI: 10.1017/s002217240004153x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting lecithinase activity and production inClostridium welchii

Abstract: SUMMARYA variety of factors that affect lecithinase activity and lecithinase production byCl. welchiiwere studied. The lecithinase activity was time and temperature dependent. The optimum temperature varied from 30° to 46° C. according to the strain ofCl. welchiiemployed. Maximum lecithinase activity was produced after 12–60 hr. There was considerable strain variation. This could easily account for the differences in the published data.Commercial purified lecithinase was more readily destroyed by heat than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1970
1970
2013
2013

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Induction of phospholipase C by lecithin has been reported (Nakamura et al 1969) but this was not confirmed (Table 2). Pivnick et al (1964) and Hauschild (1966) reported that yields of alpha-and theta-haemolysin as well as epsilon-and kappa-toxins from C. perfringens type C and D were higher upon growth in static culture with pH control than in cultures without.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Induction of phospholipase C by lecithin has been reported (Nakamura et al 1969) but this was not confirmed (Table 2). Pivnick et al (1964) and Hauschild (1966) reported that yields of alpha-and theta-haemolysin as well as epsilon-and kappa-toxins from C. perfringens type C and D were higher upon growth in static culture with pH control than in cultures without.…”
Section: Discussionmentioning
confidence: 87%
“…2). The optimum temperature for alpha-toxin synthesis was studied by Nakamura et al (1969) who found great variations between different strains. Our results (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weiss & Strong (200) also reported toxin activity to be reduced more at 75°C than at 100°e. These observations could not be completely confirmed by Nakamura, Schulze & Cross (130) and Nakamura & Cook (126).…”
Section: Factors That Affect Alpha Toxin Activitymentioning
confidence: 77%
“…Gale & van Heyningen (43) stated that, in the absencc of glucosc, best production oc curred at pH 6.0, whereas in the presence of glucose this occurred at pH 7.0-7.5. The data of Nakamura et al (130) suggest that the optimal pH for growth and alpha toxin production may depend upon the strain of C. per fringens studied. For example, strain BP6K produced alpha toxin over a pH range of 5.5-8.5 with a maximum at pH 6.5-7.5, while strain Hobbs 3 syn thesized it at pH 6.5-7.5 with a maximum at pH 6.5.…”
Section: Factors That Affect Alpha Toxin Productionmentioning
confidence: 99%